Estimated of selection gain for productivity in progenies of sugarcane - Dutra Filho, João de Andrade; Bastos, Gerson Quirino; Machado, Paulo Rocha; da Silva, Leonam José; Simões Neto, Djalma Euzébio; Chaves, Andréa; da Silva, Frank Sinatra Gomes (Comunicata Scientiae, 2012)
The objective this study was evaluate the agroindustrial performance, estimate genetic parameters and selection gain for productivity in progenies of sugarcane under field conditions. The experiment was carried out at the Factory Saint José, Igarassu (PE), during the 2008/2009 growing season. The experiment was conducted in a completely randomized block design, and five replicates. The variables were: TCH, TPH, PC, BRIX, ATR and ATR t/ha. The analysis of variance and estimate of genetic parameters were performed. To estimate the selection gain, was used the method of direct selection. The F test showed significance and high estimate of mean heritability for TCH, TPH and ATR t/ha variables, indicating the possibility of successful selection based on those characters. Through the group averages, evidenced by Scott and Knott test, the progeny from crosses between genotypes RB83102 x RB855035 stood out above all others when it comes to productivity. By estimating the selection gain, it was found that it is possible for the practice of direct selection obtain genetic gain is significant in relation to productivity.